The effects of an obesogenic diet on behavior and cognition in zebrafish (Danio rerio): Trait average, variability, repeatability, and behavioral syndromes. Issue 11 (15th November 2022) - Anwer, Hamza; O'Dea, Rose E.; Mason, Dominic; Zajitschek, Susanne; Klinke, Annabell; Reid, Madeleine; Hesselson, Daniel; Noble, Daniel W. A.; Morris, Margaret J.; Lagisz, Malgorzata; Nakagawa, Shinichi
Abstract: The obesity epidemic, largely driven by the accessibility of ultra‐processed high‐energy foods, is one of the most pressing public health challenges of the 21st century. Consequently, there is increasing concern about the impacts of diet‐induced obesity on behavior and cognition. While research on this matter continues, to date, no study has explicitly investigated the effect of obesogenic diet on variance and covariance (correlation) in behavioral traits. Here, we examined how an obesogenic versus control diet impacts means and (co‐)variances of traits associated with body condition, behavior, and cognition in a laboratory population of 160 adult zebrafish ( Danio rerio ). Overall, an obesogenic diet increased variation in several zebrafish traits. Zebrafish on an obesogenic diet were significantly heavier and displayed higher body weight variability; fasting blood glucose levels were similar between control and treatment zebrafish. During behavioral assays, zebrafish on the obesogenic diet displayed more exploratory behavior and were less reactive to video stimuli with conspecifics during a personality test, but these significant differences were sex‐specific. Zebrafish on an obesogenic diet also displayed repeatable responses in aversive learning tests whereas control zebrafish did not, suggesting an obesogenic diet resulted in more consistent, yet impaired, behavioral responses. Where behavioral syndromes existed (inter‐class correlations between personality traits), they did not differ between obesogenic and control zebrafish groups. By integrating a multifaceted, holistic approach that incorporates components of (co‐)variances, future studies will greatly benefit by quantifying neglected dimensions of obesogenic diets on behavioral changes. Abstract : We examined how an obesogenic versus control diet impacts means and (co‐)variances of traits associated with body condition, behavior, and cognition in a laboratory population of 160 adult zebrafish ( Danio rerio ).